Gender Analysis of Minimum Age Limits Marriage in Law Number 16 of the Year 2019 concerning Marriage in Polewali Regency Mandar - Asyrul; Rusdaya Basri; Rahmawati; Sudirman L; Agus Muchsin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Islam determines and views the importance of marriage, so that a marriage must go through and consider religious, moral and social grounds. Marriage in Islam is seen as a strong bond and an absolute commitment to social life and to being an honorable human being. One of the issues discussed and the source of Islamic teachings is the issue of marriage. In the concept of Islamic law, there is no absolute provision regarding the minimum age a person is allowed to marry. The Qur'an indicates that the person who will enter into marriage must be someone who is ready and able. This type of research is field research. According to Dedy Mulyana, field research is a type of research that studies phenomena in their natural environment. For this reason, primary data is data that comes from the field. So that the data obtained truly corresponds to the reality regarding the phenomena that exist at the research location. Based on the results of an interview with Mr. Ahmad Yasin, S.H.i (Head Binuang District KUA) then it can be concluded that marriage dispensation is an application submitted by Indonesian citizens who want to get married but are prevented by the specified age limit. They cannot marry until they obtain special permission in the form of a marriage dispensation from the religious court. According to Mr Ahmad Yasin, awareness of the marriage age limit was obtained through outreach carried out by the Ministry of Religion of Polewali Mandar Regency. Based on the results that researchers have obtained, it can be concluded regarding gender analysis of the minimum age limit for marriage in Law Number 16 of 2019 concerning marriage in Polewali Mandar Regency, Protection of Women's Rights and Welfare is important to prevent early marriage which tends to have a greater negative impact against women, such as health risks, interrupted education, and limited economic opportunities. Setting the same age limit for men and women reflects the principle of gender equality and avoids discrimination based on sex in the context of marriage in Polewali Mandar Regency.